SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170676-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Explicit Hydraulic Fracture Representation in Full Field Reservoir Simulation

Abstract: The simplest and oldest method to represent hydraulic fractures in reservoir simulation models is to use a negative skin factor for stimulated wells, the implicit representation. However, a negative skin factor approach does not capture several flow aspects that impact production significantly, especially in heterogeneous, lower permeability reservoirs. A better, more realistic, production forecast is obtained by modeling the effects of induced fractures and their associated flow patterns explicitely in the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Size of the grid blocks in an LGR depends on the purpose of the simulation job. The reasonable grid size can be designed by using the results of history matching and well test reports to verify the accurate production prediction of the constructed model [18,22]. Some studies suggested different ways to create LGRs in simulation models such as Cartesian LGR in which grid sizes change alongside the various directions [18], cylindrical LGR that mostly encompasses near-wellbore illustrating for detailed pressure distributions [23], and some other types such as hexagonal, curvilinear, hybrid Cartesian, and hybrid-hexagonal LGRs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Size of the grid blocks in an LGR depends on the purpose of the simulation job. The reasonable grid size can be designed by using the results of history matching and well test reports to verify the accurate production prediction of the constructed model [18,22]. Some studies suggested different ways to create LGRs in simulation models such as Cartesian LGR in which grid sizes change alongside the various directions [18], cylindrical LGR that mostly encompasses near-wellbore illustrating for detailed pressure distributions [23], and some other types such as hexagonal, curvilinear, hybrid Cartesian, and hybrid-hexagonal LGRs [24].…”
Section: Introductionmentioning
confidence: 99%